1998
DOI: 10.1029/97ja01985
|View full text |Cite
|
Sign up to set email alerts
|

Two substorm intensifications compared: Onset, expansion, and global consequences

Abstract: Abstract. We present observations of two sequential substorm onsets on May 15, 1996. The first event occurred during persistently negative IMF B z, whereas the second expansion followed a northward turning of the interplanetary magnetic field (IMF). While the first onset remained localized, the second event led to a major reconfiguration of the magnetotail. The two very different events are contrasted, and it is suggested that the IMF direction controls the evolution of the expansion phase after the initial on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 43 publications
(26 reference statements)
5
48
1
Order By: Relevance
“…For example, the growth of a plasma instability in the inner or midmagnetotail has been suggested to start the global reconfiguration, at a time when the current sheet has become sufficiently thin and intense during the growth phase [Pulkkinen et al, 1998a].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the growth of a plasma instability in the inner or midmagnetotail has been suggested to start the global reconfiguration, at a time when the current sheet has become sufficiently thin and intense during the growth phase [Pulkkinen et al, 1998a].…”
Section: Introductionmentioning
confidence: 99%
“…The IMF was steadily southward for about an hour, after which it turned northward. Ground magnetograms from the Canadian Auroral Network for the OPEN Program Unified Study (CANOPUS) showed two activations of almost equal intensity (~300 nT) at 0623 UT and at 0706 UT [see Pulkkinen et al, 1998]. Whereas the first activation remained localized both latitudinally and longitudinally, the second event led to widespread electrojet activityø The quasi-AL index shown in the second panel of Figure 1 shows the two activations somewhat delayed; this is caused by the strong westward electrojet in the morning sector, which masked the initial onset in the midnight sector.…”
Section: Introductionmentioning
confidence: 99%
“…The thick red line shows a smoothed dependence turned to the north and the termination of the Poynting flux transfer explains the observed sharp increase in U PC and I R1 . Pulkkinen et al (1998) merely suggested that an impaired decrease of the geomagnetic activity after the external source was switched off (IMF northward turning) could be explained by the continuing energy input due to inductive electric fields~∂B/∂t. In the substorm under study in this paper, the magnetic activity after the northward turning was still increasing (Fig.…”
Section: Discussionmentioning
confidence: 99%